Contribution of NADPH-cytochrome P450 Reductase to Azole Resistance in Fusarium oxysporum - He, Dan; Feng, Zeqing; Gao, Song; Wei, Yunyun; Han, Shuaishuai; Wang, Li (Frontiers in Microbiology, 2021)
Fusarium species exhibit significant intrinsic resistance to most antifungal agents and fungicides, resulting in high mortality rates among immunocompromised patients. Consequently, a thorough characterization of the antifungal resistance mechanism is required for effective treatments and for preventing fungal infections and reducing antifungal resistance. In this study, an isolate of F. oxysporum (wild-type) with broadly resistant to commonly antifungal agents was used to generate 1,450 T-DNA random insertion mutants via Agrobacterium tumefaciens-mediated transformation. Antifungal susceptibility test results revealed one mutant with increased sensitivity to azoles. Compared with the resistant wild-type, the mutant exhibited low MICs to KTZ, ITC, VRC, POS, and PCZ (0.125, 1, 0.06, 0.5, and 0.125μg/mL, respectively). The T-DNA insertion site of this mutant was characterized as involving 2 adjacent genes, one encoding a hypothetical protein with unknown function, and the other encoding the NADPH-cytochrome P450 reductase, referred as CPR1. To confirm the involvement of these genes in the altered azole susceptibility, the independent deletion mutants were generated and the Cpr1 deletion mutant displayed the same phenotypes as the T-DNA random mutant. The deletion of Cpr1 significantly decreased ergosterol levels. Additionally, the expression of the downstream Cyp51 gene was affected, which likely contributed to the observed increased susceptibility to azoles. These findings verified the association between Cpr1 and azole susceptibility in F. oxysporum. Furthermore, this gene may be targeted to improve antifungal treatments.